LARA

Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
Next revision
Previous revision
sav08:homework01 [2008/05/29 11:47]
barbara typo
sav08:homework01 [2015/04/21 17:30] (current)
Line 91: Line 91:
  
 Negation-normal form of a propositional formula contains only conjunction,​ disjunction,​ and negation operators. ​ Such formula should not contain implication operator. ​ Moreover, negation only can only apply to variables and not to other formulas. ​ The following tautologies can be used to transform formula to negation normal form: Negation-normal form of a propositional formula contains only conjunction,​ disjunction,​ and negation operators. ​ Such formula should not contain implication operator. ​ Moreover, negation only can only apply to variables and not to other formulas. ​ The following tautologies can be used to transform formula to negation normal form:
-\[\begin{array}{l}+\begin{equation*}\begin{array}{l}
   \lnot (p \land q) \leftrightarrow (\lnot p) \lor (\lnot q) \\   \lnot (p \land q) \leftrightarrow (\lnot p) \lor (\lnot q) \\
   p \leftrightarrow ​ \lnot (\lnot p) \\   p \leftrightarrow ​ \lnot (\lnot p) \\
Line 97: Line 97:
   \lnot (p \lor q) \leftrightarrow (\lnot p) \land (\lnot q)   \lnot (p \lor q) \leftrightarrow (\lnot p) \land (\lnot q)
 \end{array} \end{array}
-\]+\end{equation*}
 Extend the solution for the previous problem with a function that takes formula syntax tree and transforms it into an equivalent formula in negation-normal form.  For example, the function should transform formula $\lnot (p \rightarrow \lnot q)$ into formula $p \land q$. Extend the solution for the previous problem with a function that takes formula syntax tree and transforms it into an equivalent formula in negation-normal form.  For example, the function should transform formula $\lnot (p \rightarrow \lnot q)$ into formula $p \land q$.
  
Line 103: Line 103:
   * generate a random assignment to propositional variables of the formula   * generate a random assignment to propositional variables of the formula
   * compare the truth value of the original and of the transformed formula   * compare the truth value of the original and of the transformed formula
 +
  
 ===== Optional Problem 5 ===== ===== Optional Problem 5 =====
Line 108: Line 109:
 Consider [[:regular expression]]s with variables denoting subsets of $\Sigma^*$ where $\Sigma=\{0,​1\}$. ​ Define function $W$ that takes such a regular expression and replaces ​ Consider [[:regular expression]]s with variables denoting subsets of $\Sigma^*$ where $\Sigma=\{0,​1\}$. ​ Define function $W$ that takes such a regular expression and replaces ​
   * each constant 0 with some relation $r_0$ and each constant 1 with some relation $r_1$   * each constant 0 with some relation $r_0$ and each constant 1 with some relation $r_1$
-  * for each variable $L$ denoting a subset of $\Sigma^*$, replaces all of its occurrences with some relation $r_L$+  * for each variable $L$ denoting a subset of $\Sigma^*$, replaces all of its occurrences with relation ​variable ​$r_L$, denoting relations on $S$
   * replaces regular set union with relation union $\cup$   * replaces regular set union with relation union $\cup$
   * replaces concatenation with relation composition $\circ$   * replaces concatenation with relation composition $\circ$
Line 114: Line 115:
  
 For example For example
-\[+\begin{equation*}
    ​W({(p+qp)*}\,​ p) = (r_p \cup (r_q \circ r_p))^* \circ r_p    ​W({(p+qp)*}\,​ p) = (r_p \cup (r_q \circ r_p))^* \circ r_p
-\]+\end{equation*}
  
 Is it the case that that if an equality $r_1 = r_2$ holds for all values of variables representing subsets of $\Sigma^*$, then $W(r_1) = W(r_2)$ holds for all values of relation variables? ​ If so, prove it.  If not, give a counterexample. Is it the case that that if an equality $r_1 = r_2$ holds for all values of variables representing subsets of $\Sigma^*$, then $W(r_1) = W(r_2)$ holds for all values of relation variables? ​ If so, prove it.  If not, give a counterexample.